Measuring food and nutrition security of enclave people of Kurigram district in Bangladesh: Food and nutrition security of enclave people (Journal of the Bangladesh Agricultural University, 2019)
This study aims at assessing and analyzing the core food security indicators to enhance food and nutrition security of enclave people. A survey was conducted using structured questionnaire covering 120 households. Primary data were collected during July to December 2018. Middle aged persons are found to be the heads of households, average age is 48.87 years, family size is 4.38 persons, average education of household’s head is 3.55 years of schooling and dependency ratio is 0.67. The total value of family assets before enclave exchange was BDT 124752 and after enclave exchange it becomes BDT 178177. Their total land area before and after enclave exchange are respectively 75.85 and 77.60 decimal. Average annual family income is BDT 114799. Total income increases significantly with the increase in income from agriculture and labor selling activities. The yearly family expenditure increases significantly with the increase in food expenditure and total land size. The annual family expenditure is BDT 134363. Average daily per capita consumptions of rice, potato, vegetables and all food items are respectively 417.59, 75.35, 114.06 and 792.06g. Daily per capita calorie and protein intakes are respectively 1788 kcal and 55 g which are relatively lower compared to the national level. People consume almost all 12 categories of food items and average household dietary diversity score is 11.50. Food security decreases with the increase in family size and increases with the increase in food cost. Absolute poverty is 89% and hard-core poverty is 55% on the basis of direct calorie intake method. Absolute and hard-core poverty are 68% and 52% respectively on the basis of cost of basic needs method. As a policy option, the government should support and take the development initiatives of people, enhance food security status and upscale the nutrition condition of people living in the enclave.J Bangladesh Agril Univ 17(4): 574–582, 2019